Adult diphtheria in Malaysia: A case report - Loganathan, Tharani; Yusof, Mohamed Paid (Malaysian Medical Association, 2018)
In November 2016, a 28-year-old Malay man presented to the emergency department in respiratory distress, with a history of fever and sore throat. A clinical diagnosis of acute diphtheria was made and the patient was isolated and ventilated in the intensive care unit, and received diphtheria antitoxin and intravenous antibiotics. Initial laboratory findings failed to confirm diphtheria, leading to discontinuation of antibiotics and quarantine. Public health measures were reinstated after a reference laboratory cultured Corynebacterium diphtheriae. Although there was no contact with ill persons, investigation revealed incomplete immunisation history, and injection of high dose steroids prior to onset of symptoms.